Evaluasi Penerapan Problem-based Learning dalam Mengatasi Kesulitan Konsentrasi saat Pembelajaran - Edlina Pramistawati (Pendidikan Teknik Informatika dan Komputer, Universitas Sebelas Maret, 2022)
The Merdeka Curriculum adds significant changes to the field of education. After the Information and Communication Technology subject in the 2013 curriculum changed to ICT Guidance in the independent curriculum, the Information and Communication Technology subject appeared under the name Informatics. Informatics still needs to be discovered, especially for grade 7 students who have just entered junior high school. Based on observations made when the teacher gave material about Informatics, students needed to be more focused and active in learning. The teacher has yet to involve students in their learning so that students do not concentrate on learning. However, distractions arise, such as students talking to their friends, not concentrating on learning and often being allowed to leave class. So that efforts are needed so that students concentrate when learning takes place. Students are expected to be actively involved in learning activities by concentrating on learning.For this reason, researchers used a problem-based learning model using the Classroom Action Research (CAR) method. This study aims to evaluate whether the application of the Problem-Based Learning method can overcome concentration difficulties while learning in grade seventh of students of a junior high school at Blora, Central Java. This research is classroom action research with research subjects consisting of 28 class VII students consisting of 13 male students and 14 female students.